Desfechos maternos, perinatais e neonatais de gestantes hospitalizadas com covid-19. - Frota, Maria Valderlanya de Vasconcelos (2024)
At the end of 2019, in the city of Wuhan, Hubei province, China, the COVID-19 pandemic emerged, caused by SARS-CoV-2, resulting in an exponential increase in the number of infected people and causing thousands of deaths around the world. The objective of this study is to describe the maternal, perinatal and neonatal outcomes of pregnant women diagnosed with COVID-19 and examine the incidence of adverse outcomes associated with the infection in municipalities in the northern region of Sobral, in Ceará. This is research with a quantitative approach, conducted by a descriptive epidemiological study. The scenario of this study corresponds to the municipality of Sobral, in Ceará. The study population includes pregnant women exposed to COVID-19 who were admitted to reference hospitals in the municipality of Sobral, including the Hospital Regional Norte (HRN) and Santa Casa de Misericórdia de Sobral (SCMS). Women with a laboratory diagnosis of COVID-19 from March 2020 to March 2022 were included, while pregnant women transferred after diagnosis were excluded from the study, making it impossible to monitor pregnancy and newborn outcomes, and those who received the diagnosis only during the postpartum period. Data collection took place between October 2022 and January 2023. The study was carried out in two stages: the first was the identification of pregnant women based on information provided by epidemiological surveillance services and SCMS and HRN files and the second was the collection of data from pregnant women's medical records made available by the Medical Archive and Statistics Service (SAME) of the aforementioned hospitals. The collected data were entered into an electronic spreadsheet, organized using Microsoft software. Excel® 2017 and subsequently processed and analyzed with the aid of the Statistical Package for the Social Sciences (SPSS) software version 23. Data analysis involved the use of measures of central tendency, dispersion and separatrices (mean, standard deviation and median ) for numerical variables, while nominal variables were analyzed using simple and relative frequency. This study is approved by the UVA Research Ethics Committee, with the Certificate of Presentation for Ethical Appreciation (CAAE). In the period from March 1, 2020 to March 31, 2022, 1058 births were carried out at the Maternity Hospital of the Hospital Santa Casa de Misericórdia de Sobral (SCMS) and 3614 at the Hospital Regional Norte (HRN), totaling 4672 births in this period. Within this group, 218 pregnant women received apositive diagnosis for COVID-19, with 108 admissions to SCMS and 110 to HRN. Of these pregnant women, 58 (26.6%) had some comorbidity. In relation to the sociodemographic characteristics of the sample in this study, an average age of 28.1 ± 7.0 years was observed, with 78.9% being mixed race, 49.5% housekeeping as their main activity, 40.4% with completed high school and 74.3% reside in the ADS of Sobral. Regarding gestational characteristics, 87.6% received prenatal care. Additionally, 14.2% had pregnancy-specific hypertensive syndrome (GHS) and 12.4% developed gestational diabetes (GDM). Regarding gestational age conditions, 50% were full-term, 46.3% were premature, 76.3% of births were cesarean sections, 78.8% of newborns had an APGAR score greater than 7 in the first minute and 90.6% after the fifth minute. Furthermore, 29% needed ICU and 30.7% needed oxygen therapy. There was also evidence of 12 cases of maternal deaths and 9 cases of neonatal deaths or losses. The development of this study contributed to the recognition of unfavorable outcomes in women positive for COVID-19 given the repercussions arising from the scenario, leading to significant changes in the health care of this population. These changes are supported by scientific evidence, which helps health professionals in the context of primary health care.